Vers une meilleure compréhension de la relation entraîneur-entraîné(s) : une revue systématique de la littérature issue du modèle des 3+1Cs - Roux, V.; Trouilloud, D. (Movement & Sport Sciences - Science & Motricité, 2021)
For more than 15 years, the 3+1Cs model (Jowett, 2007) has been proposing an analysis of the psycho-sociological processes involved in the coach-athlete relationship (CAR) in a sport context, using the concepts of closeness, commitment, complementarity, and co-orientation. The purpose of this article is to present a systematic review of the scientific literature based on this model. Fifty-nine references have been included, and examined under three main issues: the measurement of the quality of CAR, its consequences, and its potential antecedents. Overall, the results indicate that athletes` and coaches` perceptions of the quality of their relationship are associated with motivational, emotional, interpersonal, and behavioral antecedents and consequences. These results thus support the relevance of the 3+1Cs model for the analysis and understanding of the CAR. This systematic review also identified some limitations and grey areas in the current literature, suggesting that future work is needed to expand knowledge about the dynamics and level of causality between the CAR quality and certain variables, and about the role played by the level of interdependence between the athlete and coach perspectives.